Peran Orang Tua dalam Mensukseskan Pembelajaran Daring pada Masa Pandemi Covid-19 di Kelas III Sekolah Dasar - Dyah Istiadaningsih; Adisel Adisel; Septi Fitriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the extent of the role of parents in the success of the online learning system during the COVID-19 pandemic in class III of the Darul Ilmi Integrated Islamic Elementary School, Bukit Makmur Village, Pinang Raya District, North Bengkulu Regency. This study uses qualitative methods with descriptive analysis and data collection techniques using observation, interviews, and documentation. The results of this study are parents have played an active role in the success of the online learning system during the COVID-19 pandemic in class III Darul Ilmi Elementary School. It can be concluded that parents have played an active role in the success of the online learning system during the covid-19 pandemic in class III Darul Ilmi Elementary School. Keywords: Parents, Online Learning System, Covid-19